Correction: Synergism between genome sequencing, tandem mass spectrometry and bio-inspired synthesis reveals insights into nocardioazine B biogenesis. Issue 35 (21st September 2015) - Alqahtani, Norah; Porwal, Suheel K.; James, Elle D.; Bis, Dana M.; Karty, Jonathan A.; Lane, Amy L.; Viswanathan, Rajesh
<x xml:space="preserve">Abstract</x> Correction for 'Synergism between genome sequencing, tandem mass spectrometry and bio-inspired synthesis reveals insights into nocardioazine B biogenesis' by Norah Alqahtani et al., Org. Biomol. Chem., 2015, 13, 7177–7192.